n Ondersoek na die proteienvereistes van wit Leghornhenne - De Jongh, J. H.(Johannes Hendrik) (Stellenbosch : Stellenbosch University, 2012)
Proefskrif (M. Sc. Agric.) -- Universiteit van Stellenbosch, 1972.